2017
DOI: 10.1371/journal.pone.0175639
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Adhesin P (SadP) contributes to Streptococcus suis adhesion to the human intestinal epithelium

Abstract: BackgroundStreptococcus suis is a zoonotic pathogen, causing meningitis and septicemia. We previously demonstrated that the gastrointestinal tract (GIT) is an entry site for zoonotic S. suis infection. Here we studied the contribution of Streptococcal adhesin Protein (SadP) to host-pathogen interaction at GIT level.MethodsSadP expression in presence of Intestinal Epithelial Cells (IEC) was compared with expression of other virulence factors by measuring transcript levels using quantitative Real Time PCR (qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…The isolates differed by an inserted region, with genes which were likely inserted as a whole, but the origin of this inserted sequence is not well understood. The isolates also had different SadP genes, previously characterized as an adhesin as well as a factor H binding protein which may contribute to zoonotic potential (Ferrando et al, ) and is considered a putative virulence factor of S. suis (Kouki et al, ; Pian et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates differed by an inserted region, with genes which were likely inserted as a whole, but the origin of this inserted sequence is not well understood. The isolates also had different SadP genes, previously characterized as an adhesin as well as a factor H binding protein which may contribute to zoonotic potential (Ferrando et al, ) and is considered a putative virulence factor of S. suis (Kouki et al, ; Pian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…to zoonotic potential (Ferrando et al, 2017) and is considered a putative virulence factor of S. suis (Kouki et al, 2011;Pian et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If S. suis meningitis is suspected, cultures of cerebrospinal fluid (CSF) are recommended, while at the suspicion of septicaemia -blood cultures [25]. Columbia agar plates supplemented with 5% defibrinated sheep blood and Todd-Hewitt Broth are recommended for the culture of S. suis, both for diagnostic and research purposes [14,26]. Colonies of S. suis grown on blood agar after 24 hrs of incubation at 37 °C are small (0.5-1.0 mm diameter), greyish or transparent, and slightly mucoid.…”
Section: Species Characteristics and Identification Methodsmentioning
confidence: 99%
“…Invasive S. suis strains are limited only to certain STs and CCs. Of which, S. suis serotype 2 (SS2) isolates belonging to MLST clonal complex 1 (SS2/CC1) are considered highly virulent and zoonotic [26].…”
Section: Species Characteristics and Identification Methodsmentioning
confidence: 99%
“…4). Ferrando et al [64] showed that Streptococcal Adhesin P (SadP) contributes to Streptococcus suis adhesion to the human and porcine intestinal epithelial cells (IEC) and to its translocation across the human IECs. According to authors, SadP is a bifunctional protein with host-cell adhesion and host immune evasion properties.…”
Section: Other Virulence Factorsmentioning
confidence: 99%